A Note on the Tension between Silent Elements and Lexical Ambiguity, with Special Reference to Inalienable Possession - Kayne, Richard (Arborescences, 2020)
A number of examples of antecedentless deletion are discussed. In each, the presence of silent elements simplifies the interpretation, in the sense that the interpretive component can now read, in a direct way, more off the syntax than it could have in the absence of those silent elements.